PRIORITAS PERBAIKAN PRODUK MENGGUNAKAN METODE CSI (CUSTOMER SATISFACTION INDEX) DAN IPA (IMPORTANCE PERFOMANCE ANALYSIS) DI KAFE XYZ COFFEE KOTA SERANG - Ali Maksum (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2022)
The increasing number of coffee shops in Serang City has an impact on the level of competition in the business, resulting in fluctuations in sales of each product. Efforts that can be made to win the competition are that it is necessary to analyze the level of satisfaction and interests of consumers using the marketing mix to determine the strengths and weaknesses of services and products. The methods used to measure satisfaction levels and improve attributes in this study are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). This study aims to: 1) Identify Kiara Coffee consumer profiles; 2) Know the priority of attribute improvement with Customer Satisfaction Index and Importance Performance Analysis. Determination of respondents in this study using random sampling technique, with a total of 125 respondents. Data analysis used was descriptive analysis to determine consumer profiles, validity and reliability tests for questionnaire trials, Importance Performance Analysis (IPA), suitability level tests, and Customer Satisfaction Index (CSI). The results of consumer identification show that Kiara Coffee consumers are dominated by consumers who are domiciled in Serang City (78.4%), women (53.6%), aged around 21-25 years (64%), unmarried (90.4%) %), graduated from high school (20.8%), worked as a student (73.6%), had an income < IDR 1,000,000 (47.2%), and last visited Kiara Coffee < 1 week ago (47 ,2%). Based on the Importance Performance Analysis (IPA), the attribute that has the highest level of satisfaction is the cleanliness of the place (5.75). While the attribute that has the highest level of importance is product cleanliness (6.39). The value of the customer satisfaction index obtained is 76.25%. This value indicates that the customer satisfaction index is included in the